Residual sisal fibers treated by methane cold plasma discharge for potential application in cement based material - Barra, B. N.; Santos, S. F. [UNESP]; Bergo, P. V.A.; Alves, C.; Ghavami, K.; Savastano, H. (Elsevier, 2015)
The use of residual sisal fiber is becoming more frequent as reinforcement element in organic or inorganic matrix due to its low cost, high abundance in some countries and constitutes a renewable material. However, a significant loss in the mechanical performance in long term has been observed in fiber-cement composites after natural aging. These alternative fibers can be utilized in a hybrid fiber-cement in order to decrease the content of traditionally used synthetic fibers. The objective of this work was to evaluate the potential of the methane cold plasma treatment of 10 min duration on structural and physical properties of the residual sisal fibers to mitigate the degradation mechanisms when applied to cementitious matrices. Moisture sensitivity evaluation by capacitance method, dielectric measurements, X-ray diffraction, Fourier transform infrared (FTIR), spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), atomic force microscopy (AFM), angle contact and pullout test were carried out in order to follow the effect of the proposed treatment. Besides, mechanical behavior of untreated and treated sisal fibers was evaluated before and after accelerated aging in cementitious solution at 60. °C by 72 h. The results obtained in all these tests confirmed the high potential of the methane cold plasma treatment to delay the degradation of the residual sisal fibers in the presence of a Portland cement environment and these fibers present the higher pullout load and shear stress than one untreated.
Keywords: Capacitance; Contact angle; Dielectric constant; Lignocelulosic fibers; Portland cement